The impact of pre-task planning on speaking test performance for English-medium university admission. (October 2019) - O'Grady, Stefan
This study investigated the impact of different lengths of pre-task planning time on performance in a test of second language speaking ability for university admission. In the study, 47 Turkish-speaking learners of English took a test of English language speaking ability. The participants were divided into two groups according to their language proficiency, which was estimated through a paper-based English placement test. They each completed four monologue tasks: two picture-based narrative tasks and two description tasks. In a balanced design, each test taker was allowed a different length of planning time before responding to each of the four tasks. The four planning conditions were 30 seconds, 1 minute, 5 minutes, and 10 minutes. Trained raters awarded scores to the test takers using an analytic rating scale and a context-specific, binary-choice rating scale, designed specifically for the study. The results of the rater scores were analysed by using a multifaceted Rasch measurement. The impact of pre-task planning on test scores was found to be influenced by four variables: the rating scale; the task type that test takers completed; the length of planning time provided; and the test takers' levels of proficiency in the second language. Increases in scores were larger on the picture-based narrative tasks than on the two description tasks. The results also revealed a relationship between proficiency and pre-task planning, whereby statistical significance was only reached for the increases in the scores of the lowest-level test takers. Regarding the amount of planning time, the 5-minute planning condition led to the largest overall increases in scores. The research findings offer contributions to the study of pre-task planning and will be of particular interest to institutions seeking to assess the speaking ability of prospective students in English-medium educational environments.